Sirolimus for Vincristine‐Resistant Kasabach–Merritt Phenomenon: Report of Eight Patients - Wang, Huaijie; Duan, Yitao; Gao, Ya; Guo, Xinkui (Pediatric dermatology, 2017)
Background The use of sirolimus for patients with multidrug‐resistant Kasabach–Merritt phenomenon (KMP) has been reported in recent years. We present the experience of a single center in treating vincristine‐resistant KMP using sirolimus alone. Methods Children with vincristine‐resistant KMP who were treated with oral sirolimus alone were eligible for inclusion in the study. We evaluated responses according to graded response criteria and acute toxicities according to the National Cancer Institute Common Toxicity Criteria. Results Between March 2012 and October 2014, eight patients underwent sirolimus treatment. The response rate of hematologic parameters was 100% (8/8). Three tumors shrank enough to allow excision. The tumors were resected after hematologic parameters normalized. Of the five patients with unresectable vascular lesions, three had complete response, and two had partial response of their tumors at the completion of long‐term (39.7 ± 24.4 wks) sirolimus treatment. Grade 3 or 4 adverse events were not documented during treatment or follow‐up. No recurrence or progression of the disease was observed during follow‐up. Conclusion In this small case series, we found sirolimus to be highly effective, with minimal side effects, for vincristine‐resistant KMP. A larger study to compare sirolimus and vincristine for KMP is warranted.